High temperature resistant and high thermal conductivity PA10T
By introducing multi-layer thermally conductive particles, the performance problems of PA10T materials in processing and high-temperature environments are solved, and the PA10T composition that is resistant to high temperature and high heat conductivity is achieved, extending the service life of LED lamps.
Patent Information
- Application Number
- CN202310422992.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-20
AI Technical Summary
PA10T material has high viscosity during processing, making it difficult to blend and modify with other general polymers, and is easy to soften and brittle under high temperature environments, reducing the service life of LED lamps.
Using multi-layer thermally conductive particles, including innermost alumina particles, intermediate aminated silica and outermost PA10T oligomer, the high temperature and thermal conductivity of PA10T is improved through efficient thermal conductivity and reinforcement fillers.
It effectively reduces the processing temperature of PA10T, improves its blending and modification ability with other materials, enhances thermal conductivity and high temperature resistance, and extends the service life of LED lamps.
Smart Images

Figure BDA0004187500670000051
Abstract
Description
Technical Field
[0001] The invention relates to an engineering plastic, in particular to high-temperature-resistant and high-thermal-conductivity PA10T. Background Art
[0002] Compared with incandescent lamps, LED lamps require lower voltage, consume less energy, are smaller in size, have a faster effect, and have a longer service life. They have gradually replaced incandescent lamps in many applications and have become a widely used light source.
[0003] LED lamps have high light energy conversion efficiency, but their lifespan is greatly affected by the operating temperature. When the operating temperature of LED lamps increases from 115℃ to 135℃, their service life will drop sharply from 50,000 hours to 20,000 hours, greatly reducing the performance of LEDs. Therefore, LED lamps need to be used in conjunction with thermal conductive materials to transfer the generated heat in time and extend the life of LED lamps. At the same time, the operating temperature of LED lamps is also high. Ordinary plastics will soften, become brittle, or even degrade in a long-term high temperature environment, which also greatly reduces the service life of LED lamps.
[0004] The ideal material that can meet the requirements of high temperature resistance and high thermal conductivity is metal or alloy, such as aluminum alloy, stainless steel, etc. However, metal has the disadvantages of high specific gravity and electrical conductivity, and is not suitable as a material for LED lamps. PA10T has good dimensional stability and high temperature resistance, and can be used in LED lamps. It can also be blended with functional fillers to give new properties based on the high performance of PA10T.
[0005] CN113462152A discloses an insulating heat-conducting composite material for LED lamp cups, comprising: 35% to 50% nylon resin; 25% to 55% heat-conducting agent; 8% to 20% alkali-free glass fiber; 2% to 8% toughening agent; 0.2% to 0.5% silane coupling agent; 0.3% to 2% lubricant; and 0.2% to 0.5% antioxidant; wherein the heat conductivity of the heat-conducting agent in the in-plane direction is at least 30W / m·K. CN110922749A discloses a highly weather-resistant and highly reflective polyamide composite material for LEDs, the raw materials of which include 30 to 70 parts of semi-aromatic polyamide, 5 to 30 parts of titanium dioxide, 5 to 30 parts of potassium titanate whiskers, 1 to 15 parts of nano metal oxides, 0.1 to 5 parts of hydrolysis-resistant agents, 0.1 to 5 parts of light stabilizers, 0.1 to 2 parts of nucleating agents, and 0.1 to 5 parts of processing aids. CN109661554A discloses a heat sink for LED, the raw material of which is a polymer composition comprising polyamide, thermally conductive particle material, epoxy functionalized olefin copolymer and inorganic fiber.
[0006] As an emerging functional plastic in the LED field, PA10T has great performance advantages. However, at the same time, PA10T currently has the following technical problems that need to be solved urgently: 1) PA10T has a high processing temperature and is difficult to blend and modify with other general polymers, resulting in slow progress in the functional modification of PA10T; 2) PA10T has high viscosity during processing, and its blended inorganic particles are difficult to disperse, especially particles such as thermal conductors, which are prone to agglomeration under high shear processing conditions, resulting in performance loss; 3) PA10T, as a material for LED lamps, needs to maintain high high temperature resistance for a long time to increase the service life of LED lamps.
[0007] Therefore, there is currently a demand for functionalization of PA10T materials in the LED field with high temperature resistance and high thermal conductivity. Summary of the invention
[0008] The object of the present invention is to provide a high temperature resistant and high thermal conductive PA10T composition.
[0009] To achieve the above objectives, the present invention provides a high temperature resistant and high thermal conductivity PA10T composition.
[0010] A high-temperature-resistant and high-thermal-conductivity PA10T composition comprises PA10T, multi-layer thermal-conductive particles, reinforcing fillers, antioxidants, lubricants, and other additives.
[0011] In a preferred embodiment, the composition includes 100 parts by weight of PA10T, 20 to 100 parts by weight of multilayer thermally conductive particles, 0 to 100 parts by weight of reinforcing filler, 0 to 20 parts by weight of antioxidant, 0 to 20 parts by weight of lubricant, and 0 to 30 parts by weight of other additives.
[0012] The innermost layer of the multilayer thermal conductive particles is aluminum oxide particles, the middle layer is amino silicon dioxide, and the outermost layer is PA10T oligomer.
[0013] The particle size of the innermost layer of aluminum oxide particles is 1 μm to 100 μm, preferably 2 μm to 80 μm, more preferably 3 μm to 50 μm, more preferably 5 μm to 30 μm, and more preferably 10 μm to 20 μm.
[0014] The thickness of the intermediate layer is 1 μm to 30 μm, preferably 5 μm to 20 μm, and more preferably 10 μm to 15 μm.
[0015] The intermediate layer is formed by curing tetraethyl orthosilicate and aminopropyltriethoxysilane.
[0016] The thickness of the outermost layer is 1 μm to 30 μm, preferably 5 μm to 20 μm, and more preferably 8 μm to 10 μm.
[0017] The number average molecular weight of the PA10T oligomer in the outermost layer is 5000 or less, preferably 3000 or less, and more preferably 2000 or less.
[0018] The outermost PA10T oligomer is preferably a carboxyl-terminated PA10T oligomer.
[0019] The preparation method of the multilayer thermally conductive particles is as follows:
[0020] S1. Disperse alumina particles in ethanol.
[0021] S2. Add tetraethyl orthosilicate and aminopropyl triethoxysilane to the above dispersion to form amino-silica-coated alumina particles on the surface of the alumina particles.
[0022] S3. Adding PA10T prepolymer to the mixed solution, drying and curing after sufficient reaction, so that the PA10T prepolymer is coated on the surface of the amino-silica-coated alumina particles to form multi-layer thermally conductive particles.
[0023] The amount of the multilayer thermally conductive particles is preferably 30 to 70 parts by weight, more preferably 40 to 60 parts by weight, and even more preferably 50 parts by weight.
[0024] The reinforcing filler is selected from fibrous fillers or powdery fillers.
[0025] The fibrous filler is selected from one or more of glass fiber, ceramic fiber, basalt fiber, carbon fiber, zinc oxide whisker, calcium sulfate whisker, and carbon nanotube.
[0026] The powdered filler is selected from one or more of wollastonite, mica, muscovite, talc, clay, bentonite, montmorillonite, clay, silicon nitride, boron nitride, graphene, graphite, alumina, silicon dioxide, titanium dioxide, ferrous oxide, zirconium oxide, calcium carbonate, calcium sulfate, barium sulfate, magnesium hydroxide, calcium hydroxide, and aluminum hydroxide.
[0027] The reinforcing filler is present in an amount of 10 to 80 parts by weight, preferably 20 to 50 parts by weight, and more preferably 30 to 40 parts by weight.
[0028] The antioxidant is selected from one or more of hindered phenol antioxidants and phosphite antioxidants, the hindered phenol antioxidant is selected from one or more of antioxidant 1010, antioxidant 1035, antioxidant 1330, and antioxidant 259, and the phosphite antioxidant is selected from one or more of antioxidant 168 and antioxidant 626GE. Preferably, the weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is (1-5):(1-5).
[0029] The antioxidant is preferably 1 to 3 parts by weight, preferably 2 parts by weight.
[0030] The lubricant is selected from one or more of stearate, stearamide, polyethylene wax and erucamide.
[0031] The lubricant is preferably 1 to 3 parts by weight, preferably 2 parts by weight.
[0032] The other additives include colorants, reflective fillers, UV absorbers, antioxidants, leveling agents, and the like.
[0033] The lubricant is preferably 1 to 25 parts by weight, preferably 5 to 20 parts by weight, and preferably 10 to 15 parts by weight.
[0034] The present invention also provides a method for preparing a high temperature resistant and high thermal conductivity PA10T composition, comprising the following steps.
[0035] The above raw materials are added into a high-speed mixer and stirred and mixed evenly. The mixed materials are added into the twin-screw extruder from the main feeding port of the twin-screw extruder, melt-mixed, extruded and granulated to obtain the high temperature resistant and high thermal conductivity PA10T composition.
[0036] The speed of the high-speed mixer is 200-2000 rpm, and the mixing time is 5-20 min. The extrusion granulation also includes extrusion, drawing, cooling, pelletizing, and drying. The processing temperature of the melt mixing is 300-330°C.
[0037] Compared with the prior art, the present invention has the following beneficial effects.
[0038] The present invention introduces multi-layer thermal conductive particles into the PA10T composition, including a multi-layer structure, wherein the innermost layer is aluminum oxide particles, the middle layer is amino silica, and the outermost layer is PA10T oligomer. The innermost layer of aluminum oxide can serve as a thermal conductive core to transfer the heat generated by the operation of the LED in real time, so that it cannot accumulate in the PA10T material, thereby extending the service life. The amino silica in the middle layer is both a good wrapping material that can achieve good coating properties for aluminum oxide; silica has excellent rigidity and can improve the high temperature resistance of PA10T; the amino silica can also functionalize aluminum oxide and provide amino active groups as connection sites with the outer layer of PA10T oligomers, thereby enhancing the dispersion effect of the PA10T oligomers on the multi-layer thermal conductive particles. The outermost layer is PA10T oligomer, which is compatible with the matrix resin to a great extent. In the process of preparing the particles, PA10T oligomer can react with the silanol or silaneoxy groups and free amino groups that have not reacted completely during the amino silica coating process, so that the particle surface is completely coated with PA10T oligomer, thereby improving the dispersibility of the multi-layer thermal conductive particles. DETAILED DESCRIPTION
[0039] The following is a further description of the implementation of the present invention in conjunction with specific embodiments. People familiar with the technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0040] Before further describing the specific embodiments of the present invention, it should be understood that the scope of the present invention includes, but is not limited to, the following specific embodiments. Generally, the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are generally performed under conventional conditions or under conditions recommended by the manufacturers.
[0041] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0042] Example
[0043] Take alumina particles with an average particle size of about 15 μm and disperse them in 95% ethanol. Add tetraethyl orthosilicate and aminopropyl triethoxysilane in a mass ratio of 5:1 to the above dispersion, add a few drops of hydrochloric acid to adjust the pH to 3-4, heat to 50°C, react for 3 hours, so that tetraethyl orthosilicate and aminopropyl triethoxysilane form amino silica coated alumina particles on the surface of the alumina particles. The generated particles are filtered, washed with ethanol, and vacuum dried at room temperature to obtain dry amino silica coated alumina particles. The above particles are mixed with a carboxyl-terminated PA10T prepolymer with a molecular weight of 1000-2000, a few drops of hydrochloric acid are added, the temperature is raised to 80-100°C, and the reaction is further performed for 4 hours, so that the PA10T prepolymer is coated on the surface of the amino silica coated alumina particles to form a coating. Finally, the multilayer thermally conductive particles were repeatedly washed three times with ethanol and water, and then vacuum dried at 80° C. for 6 h to make the particles dense and form multilayer thermally conductive particles.
[0044] Take 100 parts by weight of PA10T, 50 parts by weight of multilayer thermal conductive particles, 30 parts by weight of glass fiber, 1 part by weight of antioxidant 1010, 1 part by weight of antioxidant 168, and 2 parts by weight of polyethylene wax, and mix them evenly in a high-speed mixer. Add the mixed materials into the twin-screw extruder from the main feeding port of the twin-screw extruder, melt-mix, and extrude and granulate to obtain the high temperature resistant, high thermal conductive and PA10T composition. The processing temperature of the melt mixing is 300-330°C.
[0045] The amount of raw materials in each layer was adjusted to obtain multilayer thermal conductive particles with different layer thicknesses as shown in Table 1. The thickness of each layer was determined by TEM, and the degree of agglomeration was judged.
[0046] Table 1
[0047]
[0048] The amino silica in the multilayer thermally conductive particles mainly serves to coat the alumina and realize its functionalization, providing amino active groups as connection sites with the outer layer of PA10T. As can be seen from Examples 1-4 and 7, the thickness of the amino silica layer can effectively improve the thermal conductivity of the material within a certain range, and the inorganic particles can be used as a rigid blending component to improve the melting point of the material. In Example 7, there is a lack of an amino silica layer, which means that even if the PA10T coating process is performed on it, the PA10T prepolymer cannot be grafted onto the alumina. In the TEM photo, no grafting layer can be seen on the surface of the alumina, and the particles are agglomerated in the material, which leads to defects in the material, which not only affects the thermal conductivity of the alumina, but also reduces the melting point of the material.
[0049] PA10T mainly plays the role of promoting dispersion. It can react with the silanol or silaneoxy groups and free amino groups that have not reacted completely during the amino silica coating process, so that the particle surface is completely coated with PA10T oligomers, thereby improving the dispersibility of the multilayer thermally conductive particles. It can be seen from Examples 2, 5-6, and 8 that the thickness of the PA10T prepolymer can effectively improve the thermal conductivity and melting point of the material within a certain range. In Example 6, the thickness of PA10T is too large, resulting in the particle size of the multilayer thermally conductive particles being too large, increasing the spacing between particles and reducing the thermal conductivity of alumina. However, when the thickness of PA10T is too large, the effect on the melting point is small. This may be because the PA10T layer is well compatible with the substrate and has little effect on its crystallization and other properties. Example 8 is not coated with PA10T prepolymer, and the alumina particles agglomerate during the processing. The defects caused by agglomeration cause the thermal conductivity of the material to decrease, and the melting point also decreases, and the thermal conductivity and enhancement of alumina cannot be fully exerted.
[0050] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A high temperature resistant and high thermal conductivity PA10T composition, characterized in that: Including PA10T, multi-layer thermal conductive particles, reinforcing fillers, antioxidants, lubricants, and other additives; The innermost layer of the multilayer thermally conductive particles is aluminum oxide particles, the middle layer is amino silicon dioxide, and the outermost layer is PA10T oligomer; The thickness of the middle layer is 1 μm to 30 μm; the thickness of the outermost layer is 1 μm to 30 μm.
2. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The particle size of the innermost layer of aluminum oxide particles is 1 μm to 100 μm.
3. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The innermost layer of aluminum oxide particles has a particle size of 2 μm to 80 μm.
4. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The particle size of the innermost layer of aluminum oxide particles is 3 μm to 50 μm.
5. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The particle size of the innermost layer of aluminum oxide particles is 5 μm to 30 μm.
6. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The innermost layer of aluminum oxide particles has a particle size of 10 μm to 20 μm.
7. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The thickness of the intermediate layer is 5 μm to 20 μm.
8. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The thickness of the intermediate layer is 10 μm to 15 μm.
9. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The thickness of the outermost layer is 5 μm to 20 μm.
10. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The thickness of the outermost layer is 8 μm to 10 μm.
11. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The number average molecular weight of the outermost layer PA10T oligomer is 5000 or less.
12. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The number average molecular weight of the outermost layer PA10T oligomer is 3000 or less.
13. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The number average molecular weight of the outermost layer PA10T oligomer is 2000 or less.
14. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 1, characterized in that: The invention comprises 100 parts by weight of PA10T, 20 to 100 parts by weight of multilayer thermal conductive particles, 0 to 100 parts by weight of reinforcing filler, 0 to 20 parts by weight of antioxidant, 0 to 20 parts by weight of lubricant and 0 to 30 parts by weight of other auxiliary agents.
15. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 14, characterized in that: The multilayer thermally conductive particles are 30 to 70 parts by weight.
16. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 14, characterized in that: The multilayer thermally conductive particles are 40 to 60 parts by weight.
17. A high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 14, characterized in that: The multilayer thermally conductive particles are 50 parts by weight.
18. A method for preparing a high temperature resistant and high thermal conductivity PA10T composition according to any one of claims 1 to 17, characterized in that: The steps include: The raw materials are added into a high-speed mixer and stirred to mix evenly; the mixed materials are added into the twin-screw extruder from the main feeding port of the twin-screw extruder, and after melt mixing and extrusion granulation, the high temperature resistant and high thermal conductivity PA10T composition is obtained.
19. A method for preparing a high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 18, characterized in that: The extrusion granulation also includes the steps of extrusion, strand drawing, cooling, pelletizing and drying.
20. A method for preparing a high temperature resistant and high thermal conductivity PA10T composition as claimed in claim 18, characterized in that: The processing temperature of the melt mixing is 300-330°C.
21. A material for LED lamps, comprising the high temperature resistant and high thermal conductivity PA10T composition according to any one of claims 1 to 17.
Citation Information
Patent Citations
Thermally conductive polymer composition for heat sink
CN109661554A
Preparation method of high-weather-resistance and high-reflectivity polyamide composite material for LEDs
CN110922749A
LED lamp cup, insulating heat-conducting composite material and preparation method and application thereof
CN113462152A
Polyamide 10T composite thermal dissipation material with high thermal conductivity for light-emitting diode lamp, and preparation method thereof
CN104987713A
High-temperature-resistant low-shrinkage PA10T composition
CN114921095A